Substantiation of using wine-making secondary products as alternative raw material for confectionery industry - Kalinovska, Tatyana; Obolkina, Vera (My University, 2013)
The article is aimed at studying the concentration of pectin and phenol substances in grapes and in processed grapes products as well as at assessing the expediency of making them part of recipe as a valuable raw material for new kinds of confectionery.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; grape pomace; grape puree; виноградне пюре; пектин виноградний; виноградні вичавки